2019
DOI: 10.1186/s12890-019-0802-1
|View full text |Cite
|
Sign up to set email alerts
|

NK and NKT cells in the diagnosis of diffuse lung diseases presenting with a lymphocytic alveolitis

Abstract: BackgroundDiffuse lung diseases (DLD) are characterized by different immunophenotypes in the bronchoalveolar lavage fluid (BALF). We aimed to evaluate the diagnostic value of BALF NK and NKT cell counts of patients with DLD and lymphocytic alveolitis.MethodsWe assessed 202 patients with DLD, who underwent BALF immunophenotyping. Samples were routinely processed by flow cytometry and lymphocyte subsets were compared between patients with sarcoidosis (n = 106), hypersensitivity pneumonitis (HP; n = 53), and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…By contrast, witnessing the possible impact of (micro)environmental factors, active cigarette smoking, and to a lesser extent, past smoking habit, decrease the number of lung NK cells (10, 11), whereas they are rapidly and dramatically increased during influenza virus lung infection. In different inflammatory diseases, including sarcoidosis, COPD, hypersensitivity pneumonitis (29), autoimmune diseases, and idiopathic pulmonary fibrosis, however, conflicting results have been found regarding the proportions and number of NK cells within the lungs (Table 1). Irrespective of their circulating or resident nature, NK cells might be increased or decreased during these diseases.…”
Section: Lung Nk Cells In Diseasesmentioning
confidence: 99%
“…By contrast, witnessing the possible impact of (micro)environmental factors, active cigarette smoking, and to a lesser extent, past smoking habit, decrease the number of lung NK cells (10, 11), whereas they are rapidly and dramatically increased during influenza virus lung infection. In different inflammatory diseases, including sarcoidosis, COPD, hypersensitivity pneumonitis (29), autoimmune diseases, and idiopathic pulmonary fibrosis, however, conflicting results have been found regarding the proportions and number of NK cells within the lungs (Table 1). Irrespective of their circulating or resident nature, NK cells might be increased or decreased during these diseases.…”
Section: Lung Nk Cells In Diseasesmentioning
confidence: 99%
“…Natural killer (NK) cells are the core cells of the natural immune system, derived from bone marrow stem cells. They are a group of large granular lymphocytes different from T and B cells, mainly distributed in peripheral blood, liver and spleen.NK cells are part of the rst-line defense of the immune system, Lower NK% was observed in BALF from sarcoidosis than other interstitial lung diseases [30,31] .NK cells in BALF are associated with poor outcome and an advanced radiological stage.An impaired lung function was shown to be associated with a high level of NK cells in the lungs. Furthermore, sarcoidosis patients requiring steroid treatment also had a higher percentage of these cells in BALF [32] .Our study found that the proportion of NK cells in LNPF and BALF were signi cantly lower than that in PB and there was no signi cant difference in the proportion of NK cells in LNPF and BALF in sarcoidosis patients.The lower proportion of NK cells in LNPF and BALF in our study may be related to the mild condition and slight impairment of pulmonary function in our stage patients.The proportion of NK cells in LNPF and BALF may help to distinguish the sarcoidosis patients requiring steroid treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, CD3 and NK cells-associated marker CD56/16 have been used in several studies on sarcoidosis and other lung diseases to identify NK T cells. [26][27][28] NK T cells can release cytokines that can influence the balance between TH1 and TH2 responses. 29 A dysregulation of NK T cells has been proposed to, at least partly, explain the amplified T cell response in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%